Comparative study of the antioxidant effects of lavender and flax oils in recurrent aphthous ulceration treatment - Ahmed , Shaheen A.; Altaei , Taghreed; Ahmed , Talar (Journal of Baghdad College of Dentistry, 2020)
Background: Recurrent aphthous ulceration (RAU) is an inflammatory condition of unknown etiology characterized by painful recurrent (single or multiple) ulcerations of the oral mucosa. It is one of the most common and poorly understood mucosal disorders. It occurs more frequently in times of stress. Local and systemic conditions, genetic, immunologic, microbial factors, and oxidative stress may play a role in the pathogenesis of RAU. The objective of this study was to evaluate the free radical metabolism and antioxidant activity of RAU patients treated by lavender or flax oil paint. Materials and Methods: Sixty-six RAU patients were enrolled in this prospective randomized double-blind placebo-controlled study. Analysis of the plasma levels of malondialdehyde (MDA), glutathione (GSH), Nitric oxide (NO), myeloperoxidase (MPO), Vit. E, Vit. C, and Trolox equivalent antioxidant capacity (TEAC) were determined. The ulcer size, healing time, and healing process were correlated to the plasma levels of the studied parameters for the assessment of the antioxidant mechanism of action of lavender and flax oil paint in the treatment of RAU. Results: Statistical analysis showed that lavender antioxidant action was higher than flax oil paint compared to placebo. The decreased oxidative stress and the damage caused by free radicals was significant in the lavender group than both flax group and placebo (P<0.001). Conclusion: This study proves the significant antioxidant mechanism of both lavender and flax in the treatment of RAU patients. Keywords: Recurrent aphthous ulceration (RAU), oxidative stress, antioxidants, lavender, flax